2000
DOI: 10.1074/jbc.m003246200
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant of Tetrahymena Telomerase Reverse Transcriptase with Increased Processivity

Abstract: The protein catalytic subunit of telomerase (TERT) is a reverse transcriptase (RT) that utilizes an internal RNA molecule as a template for the extension of chromosomal DNA ends. In all retroviral RTs there is a conserved tyrosine two amino acids preceding the catalytic aspartic acids in motif C, a motif that is critical for catalysis. In TERTs, however, this position is a leucine, valine, or phenylalanine. We developed and characterized a robust in vitro reconstitution system for Tetrahymena telomerase and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
120
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(125 citation statements)
references
References 61 publications
5
120
0
Order By: Relevance
“…Recently, it was shown that the N-terminal domain of Tetrahymena Thermophila catalytic telomerase subunit can also bind DNA and RNA [26,27]. In human telomerase the corresponding domain [28] was shown to be crucial for telomerase processivity [29].…”
Section: So How Is the Unwinding Activity Of Est3p Utilized In Vivo?mentioning
confidence: 99%
“…Recently, it was shown that the N-terminal domain of Tetrahymena Thermophila catalytic telomerase subunit can also bind DNA and RNA [26,27]. In human telomerase the corresponding domain [28] was shown to be crucial for telomerase processivity [29].…”
Section: So How Is the Unwinding Activity Of Est3p Utilized In Vivo?mentioning
confidence: 99%
“…The stem III pseudoknot and stem-loop IV of the telomerase RNA are both required for normal levels of repeat addition processivity (Lai et al 2003;Mason et al 2003). The identity of a specific amino acid within a reverse transcriptase motif of TERT also affects repeat addition processivity (Bryan et al 2000a). Although there is generally no correlation between the mean telomere length of a given organism and the in vitro processivity of its telomerase, evidence suggests that processivity may be relevant for telomere maintenance in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Upon translation in rabbit reticulocyte lysate (RRL), Tetrahymena TERT can assemble with telomerase RNA into an active telomerase RNP (Collins and Gandhi 1998;Bryan et al 2000a) in a manner that is likely to be dependent on the action of protein chaperones (Holt et al 1999;Forsythe et al 2001). Indicative of a high degree of structural and functional complexity in telomerase, the in vitro reconstituted complex does not approach the degree of processivity of the enzyme isolated from cells (Collins and Gandhi 1998;Bryan et al 2000a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations